IMPROVING STUDENTS’ AWARENESS OF FUNCTIONAL LITERACY - Surwanti, Dita; Hikmah, Isti'anatul (English Language Teaching Educational Journal, 2019)
One of the ironic facts that existed in our society is functional illiteracy. It does not mean that people cannot read or write. People know how to read and write but are unable to understand the meaning of a text they read. Thus, this research was held to answer the question of ?How can students? awareness of functional literacy be improved?? This research applied a classroom action research. The results showed that functional literacy was not working due to several reasons such as the students? ignorance of the surroundings, misunderstanding of the instructions, and lacking reading comprehension and language mastery. Students? awareness of functional literacy was improved by implementing regular instructional announcements and reminders. The functional literacy which was also measured from the students? reading comprehension increased from the pre-test, which was 34.09, to 63.17 on the 1st cycle and 69.69 on the 2nd cycle. It can be concluded that functional literacy requires practice and habituation. Students reading comprehension and language mastery are the other matters to be considered in the success of functional literacy. The last, habituation that is directly related to daily life needs sustainable practices, not only in the classroom but also outside in order to become a habit and they can live well in the society.